PENGARUH LINGKUNGAN KERJA DAN DISIPLIN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT.RIGUNAS AGRI UTAMA KABUPATEN INDRAGIRI HULU - Reski -; Marnis -; Liswar Hamid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aim to know how Work environment variable and discipline of work productivity PT. Rigunas Agri Utama Kabupaten Indragiri Hulu. As for becoming population in this reseacrh is counted 53 people employees PT. Rigunas agri utama kabupaten indragiri hulu. Used data by analisys is descriptive, despitefully also use quantitative analisys that is using double linear regression constructively SPSS version program 16. From result of examination which have been simultan regresi test (uji-F) indicate that work environment variable and discipline by simultan have an effect on signifikan to work productivity. Result of test parsial (T-Test) indicating that work environment and discpline by parsial have an effect on signifikan of work productivity to PT. Rigunas Agri Utama Kabupaten Indragiri Hulu.Keywords: work environment, discipline, work productivity